Observer-based adaptive control for nonlinear input-delay systems with unknown control directions. Issue 8 (11th June 2019) - Ma, Jiali; Zhuang, Guangming; Cui, Guozeng; Wang, Jiaqi
ABSTRACT: This paper investigates the problem of adaptive control for strict-feedback nonlinear systems with input delay and unknown control directions. The Nussbaum function is utilised to deal with the unknown control directions and a novel compensation system is introduced to handle the time-varying input delay. By using neural network(NN) approximation and backstepping approaches, an adaptive NN controller is designed which can guarantee the semi-global boundedness of all the signals in the closed-loop system. Two simulation examples are also given to illustrate the effectiveness of the proposed method.